2015
DOI: 10.1177/0973005215572460
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Behaviour Research in Rural Producers’ Cooperatives

Abstract: Cooperatives are important organizational forms helping millions of people, particularly in rural areas, to improve their socio-economic conditions. They are also unique in that they are member-centric business organizations with democratic control, where the shareholders are also users of their services. In this article, first, I discuss the importance of cooperatives as organizational forms, particularly the rural producers’ cooperatives (RPCs); second, analyze the research trends within the organizational b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…It may, thus, be claimed that management is the principal factor affecting the performance of such cooperatives. This is consonant with the reports by Biswas 2015;Hosseini et al 2014;Osmar and Wander 2021;MacLean and MacKinnon 2000;Mhembwe and Dube 2017;Pham 2022;Zarifian and Bahadori 2014). The presence or absence of similar factors determines whether a given type of cooperative will succeed or fail (Attwood and Baviskar 1987).…”
Section: Acknowledgementsupporting
confidence: 89%
See 3 more Smart Citations
“…It may, thus, be claimed that management is the principal factor affecting the performance of such cooperatives. This is consonant with the reports by Biswas 2015;Hosseini et al 2014;Osmar and Wander 2021;MacLean and MacKinnon 2000;Mhembwe and Dube 2017;Pham 2022;Zarifian and Bahadori 2014). The presence or absence of similar factors determines whether a given type of cooperative will succeed or fail (Attwood and Baviskar 1987).…”
Section: Acknowledgementsupporting
confidence: 89%
“…found that the members' commitment and cooperative management had a greater impact on the success of cooperatives than other factors. Biswas (2015) identified members' mutual trust, commitment, beliefs and attitudes towards their cooperative and the management style adopted to be important factors affecting a cooperative's success. Gupta (2014) discovered that cooperatives offer structures that not only secure their own benefits but also guarantee the individuals' interests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the respect of a certain sense of fairness is closely related with the general framework of satisfaction and commitment (Simons and Ingram, 1997). Cooperatives tend to produce better results when they are perceived as equitable, transparent and competent in addressing their members' specific needs (Biswas, 2015;Chen et al, 2007). That is, farmers' satisfaction and commitment are inseparable from the search of a collective sense of justice and fairness in a practical implementation of moral economies (Sayer, 2007).…”
Section: Food Value Chains Cooperatives and Its Relationship With Farmers' Satisfactionmentioning
confidence: 99%